Two Novel Techniques in the Treatment of Corneal Alkaline Burns: Platelet-Rich Fibrin Membrane and Concentrated Growth Factor Membrane: A Rabbit Model - Şule Melek, Gültekin Atalan, Hayati Yüksel (Revista Electronica de Veterinaria, 2022)
To investigate the effect of platelet-rich fibrin membrane (PRFM) and concentrated growth factor membrane (CGFM) on the healing of corneal alkaline burns. 24 New Zealand rabbits were divided into four groups equally. Alkaline burn was created in the cornea of each one of the rabbits in each group. Group I: Tarsorrhaphy was applied by fixing PRFM obtained from the whole blood samples of the subjects to the lower and upper conjunctivae to cover the cornea. Group II: Tarsorrhaphy was applied by fixing CGFM obtained from the whole blood samples of the subjects to the lower and upper conjunctivae to cover the cornea. Group III: Tarsorrhaphy was applied after alkaline burn was created in the cornea. Group IV: Alkaline burn was created in the cornea and the eye was left open. Fluorescein staining was applied to the subjects in all groups and their intraocular pressure was measured using a rebound tonometer. At the end of the Day 10, all animals in the groups were killed. Histopathological staining was performed and this was compared between the groups. As a result of clinical examinations, the most healing was seen in Group I and Group II, respectively. When evaluated in terms of epithelial regeneration formation, histopathological examinations were also seen to support clinical examination results.This study revealed that the treatment of corneal alkaline burns with PRFM and CGFM contributes positively to the healing process.